Effects of cooking temperature and time on the color, morphology, crystallinity, thermal properties, starch-lipid complexes formation and rheological properties of roux. (May 2018) - Alvarez-Ramirez, J.; Vernon-Carter, E.J.; Carrillo-Navas, H.; Meraz, M.
Abstract: Roux is an equal part mixture of flour and clarified butter cooked for a few minutes, and is the basic recipe for producing sauces. There is a lack of systematic studies regarding the effects of cooking temperature and time on the characteristics of roux. To this end, roux pasta (50:50 of wheat flour and clarified butter) was prepared to assess the effects of cooking time (1, 2 and 4 min) and temperature (80 and 100 °C) on physicochemical and morphological properties. Viscosity and viscoelastic moduli increased with both temperature and cooking time, an effect ascribed to partial gelatinization of starch granules. XRD analysis showed that starch granules underwent crystallinity reduction (∼20–60%) with both cooking temperature and time. Deconvoluted FTIR indicated gradual reduction of short-range ordering with time caused by leaching out of amylose chains from starch granules, leading to the formation of amylose-lipid inclusion complexes as corroborated by DSC measurements. Also, it was found that the secondary structure of proteins was affected by cooking, with the fraction of β-sheet aggregates increasing (∼35%) upon cooking time. Overall, the above results provided a basis for understanding the very complex physicochemical changes occurring during roux manufacture. Highlights: Effects of processing conditions in physicochemical properties of roux were assessed. Starch gelatinization determines in a large extent the roux characteristics. Green color, viscosity and gelatinization increased with cooking temperature. Starch digestibility increased with cooking temperature and time. Protein secondary structure was modified by cooking.